The case against Professor Briggs - Briggs, Charles A. (Briggs heresy case, 1892)
Case against Professor Briggs, Part I. -- Case against Professor Briggs, Part II. -- Defence of Professor Briggs before the General Assembly : Case against Professor Briggs, Part III.